Sequential HIPEC, Claudin18.2-targeted therapy, and CapeOx chemotherapy leading to resolution of peritoneal metastases and curative resection in gastric cancer: a case report and literature review - Li, Weidong; Huang, Xiaodong; Han, Xiaowen; Zhang, Jiayi; Ma, Bin; Yin, Zhenyu; Wang, Yuhan; Gao, Lei; Shi, Jianming; Chen, Hao (Frontiers in Immunology, 2025)
Gastric cancer, a leading global cause of cancer-related mortality, is frequently diagnosed at advanced stages with peritoneal metastasis, significantly limiting curative options. Current strategies integrate systemic chemotherapy, hyperthermic intraperitoneal chemotherapy (HIPEC), and targeted therapies, yet outcomes remain suboptimal. Claudin18.2, a tight junction protein overexpressed in 27.4–52% of gastric cancers, has emerged as a novel therapeutic target, with recent Phase III trials demonstrating survival benefits for Claudin18.2-targeted monoclonal antibodies in HER2-negative advanced disease. However, the synergy of HIPEC with Claudin18.2-targeted therapies remains unexplored. This study presents a case of Claudin18.2-positive advanced gastric adenocarcinoma with peritoneal metastasis treated with a multimodal regimen: HIPEC, systemic CapeOx chemotherapy, and Claudin18.2-targeted therapy (ASKB589). Following 12 cycles, imaging and tumor markers (CA125, CEA) normalized, enabling curative gastrectomy. At 893 days post-diagnosis, the patient remains disease-free (PFS/DFS: 893/573 days) on adjuvant capecitabine. Treatment-related toxicities (predominantly Grade 1–3 hematologic and gastrointestinal events) were manageable. This case highlights Claudin18.2 as an actionable biomarker and proposes a “local-systemic” synergy model for peritoneal-metastatic gastric cancer. However, the absence of cytoreductive surgery and single-case limitations necessitate validation through randomized trials. Future research should prioritize biomarker-driven HIPEC protocols (e.g., nanoparticle-enhanced Claudin18.2-targeted delivery) and dynamic monitoring of Claudin18.2 expression during therapy.